Saving electricity in a hurry dealing with temporary shortfalls in electricity suppliers (OECD/IEA, 2005)
Blackouts are normally the result of imbalances in electricity supply and demand. A brief blackout is mostly an inconvenience, but persistent shortfalls--those lasting days, weeks, or months--can cause economic disruption and danger to human life in our technology-rich societies. This publication describes some of the recent power shortfalls, from Norway to New Zealand, from Tokyo to Arizona and the policies these regions used to quickly reduce their power consumption. How did the whole country of Sweden cut its power consumption by 4% in only three days? How did California save 14% in only a few months? While the temporary shortfalls in electricity supplies described in this book are relatively rare events, they disproportionately shape future energy policies. This publication shows that countries can quickly reduce electricity consumption without harming the economy as much as blackouts or unplanned curtailments. The strategies are diverse, unique and often surprisingly cheap. They include mass media campaigns--where a good joke can save a Megawatt--improvements in equipment efficiency and quickly adjusting electricity prices. This book explains how California replaced a million traffic signals with energy-saving models, how millions of Tokyo residents raised their thermostat settings, and how New Zealanders took shorter showers, all quickly enough to help avoid imminent blackouts. Finally, it connects these policies to the traditional goal of "saving electricity slowly."--publisher description.